Fast and Accurate Position Determination of Multimodal Couplings of Steel Rolling Machinery and Equipment Combined with Multimedia Optimized Particle Filters - Jian Tan (Advances in Multimedia)
During the overhaul and maintenance of the transmission system of the modern rolling mill, a very common problem is the positioning of the motor and the reducer or speed increaser. The operation of the equipment and the service life of the equipment will be significantly affected by the accuracy of the multimodal coupling position determination. Therefore, precise positioning and rapid positioning must be achieved. This article intends to analyze how this type of equipment achieves rapid and accurate positioning and what factors will affect the location determination process.